Chaetoglobosin A from Taxol-Producing Strain: Purification, Bioactivity and Structure Identification - Wu, Di; Wang, Wei; Lv, Xianyu (Asian Journal of Chemistry, 2013)
Fungi fermentation is a potential strategy for industrial production of taxol, an efficient anticancer medicine. A new taxol-producing strain has been recently isolated. A high-content, unknown secondary metabolite (herein referred to as "X") was observed from the fermentation broth. X was purified via organ extraction, high-performance liquid chromatography separation and crystallization. The purified compound X showed bio-toxic activity against Drosophila. Finally, X was identified as chaetoglobosin A through mass spectroscopy, ultraviolet spectroscopy, infrared spectroscopy and nuclear magnetic resonance with an overall consideration of the biological source.